Lying about Hitler : history, Holocaust, and the David Irving trial - Evans, Richard J. (New York, N.Y. Basic Books, 2001)
The author examines the libel suit and ensuing trial of Penguin Books UK and Deborah Lipstadt against holocaust denier David Irving. The author uses the trial to explore the question of Nazi genocide against the Jews and the roles of Hitler, Himmler and Goebbels in the Holocaust.
Preface -- History on trial -- Hitler and the Jews, 1924-1939 -- Hitler and the final solution -- Irving and Holocaust denial -- Bombing of Dresden -- In the witness box -- Judgment day.
Includes bibliographical references (pages 267-309) and index.
113524
Keywords: Irving, David John Cawdell -- 1938- -- Trials, litigation, etc; Lipstadt, Deborah E. -- Trials, litigation, etc; Irving, David, -- 1938- -- Trials, litigation, etc; Penguin (Firm) -- Trials, litigation, etc; Penguin Books -- Trials, litigation, etc; Penguin (Firm); 1939-1945; Trials (Libel) -- England -- London; Holocaust denial literature -- Great Britain; Holocaust deniers; Holocaust, Jewish (1939-1945) -- Historiography; Holocaust deniers; Historiography; Trials; Auschwitz-Luge; Trials (Libel) -- England -- London; Holocaust denial literature -- Great Britain; England -- London; Great Britain; Trial and arbitral proceedings